2020
DOI: 10.1108/rpj-04-2019-0109
|View full text |Cite
|
Sign up to set email alerts
|

An improved medial axis path generation algorithm for selective laser melting

Abstract: Purpose The principle of the medial axis calculation is complicated and difficult to implement. Moreover, the accuracy is not high. Then, as the generated path has an endpoint at the boundary of the polygon, burrs may appear on the surface of the molded piece. This paper aims to improve the warpage deformation of SLM molded parts and the surface quality of molded parts, an improved mid-axis path generation algorithm is proposed. Design/methodology/approach First, the center point is calculated by the seed po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Now, there is a large market demand. Companies, universities, and professionals are like to use intelligent translation technology to translate business English, which brings great convenience and reveals that some machine translation levels have been unable to meet the current translation needs [9]. e market urgently needs a machine translation technology with high performance and high translation accuracy [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Now, there is a large market demand. Companies, universities, and professionals are like to use intelligent translation technology to translate business English, which brings great convenience and reveals that some machine translation levels have been unable to meet the current translation needs [9]. e market urgently needs a machine translation technology with high performance and high translation accuracy [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the model is usable. m = 0.33864δ − 0.021998ω + 0.095165δω + 17.5889 (10) The response surfaces between each indicator and the factors are shown in Figure 6. Figure 6a indicates that as the support density ω increases, there is a decline in the Z-axis dimensional error E, and an evident inverse relationship exists between them.…”
Section: Analysis Of Experimental Results Of Grid-type Supportsmentioning
confidence: 99%
“…The suppression of warpage deformation during the selective laser sintering process is a crucial factor for improving workpiece forming accuracy and has been extensively studied in the field of rapid prototyping technology [ 10 , 11 ]. Zhang et al [ 12 ] found that the degree of warpage deformation of the workpiece under different scanning strategies showed significant differences and investigated the effects of varying scanning paths on workpiece warpage and surface morphology through experimental means.…”
Section: Introductionmentioning
confidence: 99%